PENGARUH LITERASI FINANSIAL, KONTROL DIRI, DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PERILAKU EKONOMI SISWA SMK PALAPA BANDAR LAMPUNG - Mohamad Ghinau Thofadillah; Novitria Amalia; Zildjian Fitri; Yuni Lestari; Cindi Yosari Saragih; Rahmawati; Suroto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The financial management skills of vocational high school students at SMK Palapa Bandar Lampung are relatively low, with an index of 55% and classified as less literate in terms of financial literacy. The purpose of this study is to determine how financial literacy, self-control, and peer environment influence the economic behavior of vocational high school students at SMK Palapa Bandar Lampung. This quantitative study uses a descriptive-verificative method, an ex post facto approach, and a survey. This study involved 30 students. Saturated sampling was used to collect samples from 30 students in grades X and XI. The coefficient of determination (R2) test, classical assumption test, multiple linear regression test, simultaneous F-test hypothesis, and Pearson's product-moment correlation formula were used to test the reliability and validity of the closed-ended questionnaire with a Likert scale. Simultaneously, the three variables (financial literacy, self-control, and peer environment) had a significant influence on students' economic behavior, with an explanatory power of 52.2% (adjusted R-square 0.522). This indicates that although financial literacy individually is not dominant, self-control and peer environment factors play a role in shaping the economic behavior of vocational high school students at SMK Palapa Bandar Lampung, while the remaining 47.8% is influenced by factors outside the scope of this study.